Production and Characterisation of Diacylglycerols from Various Edible Oil Deodoriser Distillates By Lipasecatalysed Esterification - Lo, Seong Koon (2003)
Diacylglycerols (DAG) are minor acylglycerols (< 10% w/w) found in edible oils and fats. Recently, 1 ,3-DAG has been found to prevent and manage obesity. Consequently, the novel industrial production process of 1,3-DAG was patented worldwide (US 2001/0004462) by Kao Corporation, Japan. In this work, an alternative process to produce 1 ,3-DAG was discovered. The process comprised of esterifying free fatty acids from edible oil deodoriser distillates with glycerol by using 1 ,3-position specific lipases. Deodoriser distillates from the processing of palm, soybean, canola and com oils were used. The effects of esterification reaction parameters such as the source of 1,3- position specific lipase, reaction time, lipase concentration, reaction temperature, total fatty acid to glycerol molar ratio, water and molecular sieves contents were conducted. Rhizomucor miehei lipase (Lipozyme® RM 1M) was found to be the best performing lipase. The reaction time required for optimum production of DAG is at 6 h for palm oil deodoriser distillate, and 4 to 5 h for soybean, canola and com oil deodoriser distillates. The following reaction parameters resulted in optimum yield of DAG: 10% (w/w) of Lipozyme® RM 1M, reaction temperature of 65 °C, total fatty acid to glycerol molar ratio of 2.5:1, total absence of water in the substrates, and the presence of molecular sieves of 30% (w/w). DAG yield of 60 to 72% and DAG purity of 82 to 85% were obtained. DAG produced from the deodoriser distillates and their various blends were characterised for their fatty acid and DAG compositions, iodine values (IV), thermal profiles, and slip melting points (SMP). The analytical results indicated that DAG produced from palm oil deodoriser distillate had lower degrees of unsaturation and, therefore, had higher melting points compared with that from soybean, canola and com oil deodoriser distillates. DAG produced from soybean oil deodoriser distillate had the highest degree of unsaturation. In the DAG produced from soybean, canola, and com oil deodoriser distillates, P.sitosterol, campesterol and stigmasterol were the dominant phytonutrients, while tocotrienols were the major phytonutrient in the DAG produced from palm oil deodoriser distillate. The phytosterol and vitamin E compositions in the DAG produced from the various blends varied according to the proportion of the distillate used.